Manajement Mutu Pendidik dan Tenaga Kependidikan di SMPN 1 Dlanggu Kabupaten Mojokerto - Al-Mahali, Ahmad Mustofa Jalalluddin (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The product of the teacher as a human resource is the achievement of the students and graduates of a school. These graduates must be able to compete in the world of academics and the world of work which is nothing but focusing on quality. This illustrates human resources as an important factor for success educational institutions. For this reason, the HR needs to be managed as well as possible so that it can truly be utilized for the benefit of the institution Quality Management of Educators and Education Personnel at Dlanggu 1 Public Middle School can already be said to be good with indicators of teacher achievement towards qualifications listed in the national education standard. But not enough, management functions continue to be pursued and optimized to achieve better quality or above the standard